Pemahaman Hadis Larangan Menangisi Mayit Menurut Ibnu Hajar Al-Asqalani Dalam Kitab Fatḥ Al-Bārī Syarah Shahih Al- Bukhari - M. Patuloh Fajar; Uswatun Hasanah; Hedhri Nadhiran (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Contemporary religious practices in Indonesia reveal that the prophetic prohibition against crying over the deceased is frequently interpreted in a strictly literal manner. Such an interpretation often restricts grieving families from expressing natural emotional responses, thereby generating psychological strain. This situation underscores an academic problem: a persistent disjunction between the textual formulation of the hadith and its practical reception within Muslim communities. This study therefore investigates two central questions: first, how Ibn Ḥajar al-‘Asqalānī conceptualizes the meaning of the relevant hadiths; and second, how his explanation may inform or correct literalist tendencies in present-day Indonesian Muslim society. Employing a qualitative library research method, this study examines the pertinent narrations in Ṣaḥīḥ al-Bukhārī alongside Ibn Ḥajar’s exegetical analysis in Fatḥ al-Bārī. The data were analyzed through systematic classification, interpretive reading, and thematic synthesis. The findings demonstrate that Ibn Ḥajar draws a clear distinction between natural, permissible expressions of grief and niyāhah, an exaggerated lamentation that implies objection to divine decree. He further asserts that the deceased is not punished for others’ crying unless such actions were previously sanctioned by the deceased. The study concludes that Ibn Ḥajar’s interpretive framework offers a balanced and context-sensitive understanding that can help recalibrate contemporary Muslim attitudes toward mourning practices. This highlights the importance of contextual hermeneutics in hadith interpretation.